Artificial Intelligence in Classroom Learning: Fostering Growth Mindset and Critical Thinking in the Digital Era - Mita Ariyanti; Mustika Ayu; Zulia Maharani; Ika Maryani; Muhammad Ragil Kurniawan (The Indonesian Institute of Science and Technology Research, 2026)
The rapid development of artificial intelligence (AI) has significantly transformed educational practices, especially in classroom learning environments. While AI provides opportunities for personalized learning, adaptive feedback, and enhanced engagement, concerns have also emerged regarding student dependency and reduced critical thinking skills. This study aims to explore the integration of AI in classroom learning and its relationship with growth mindset development among students. Using a qualitative descriptive approach, the research analyzes classroom learning strategies that utilize AI as a collaborative learning partner rather than as a replacement for human cognition. Data were obtained from literature studies and classroom learning observations focusing on AI-supported learning activities, critical thinking development, and growth mindset orientation. The findings indicate that AI can function effectively as a learning stimulus that encourages reflective thinking, supports student engagement, and facilitates feedback-driven learning processes. However, without proper guidance, AI may also lead to overreliance and reduced independent thinking. Therefore, teachers play a crucial role in guiding students to use AI responsibly and productively. The results show that AI integration combined with growth mindset principles can enhance learning motivation, promote resilience when facing academic challenges, and encourage collaborative knowledge construction. This research highlights the importance of pedagogical strategies that position AI as a learning partner while maintaining the central role of human reasoning and creativity in education.